In a nutshell. Practicing Good Agriculture ... the vital link ... in the food safety chain - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
This issues provides information on good agricultural practices (GAP) for fresh fruit and vegetable production in an attempt to enhance knowledge, improve farming techniques and contribute to the overall goal of producing high quality and safe food products. It is not intended as a manual to implement GAP. It is intended to introduce and educate all interested readers about food agricultural practices.